Impact of chamber pressure and material properties on the deformation response of corneal models measured by dynamic ultra-high-speed Scheimpflug imaging - Correia,Fernando Faria (2013)
PURPOSE: To study the deformation response of three distinct contact lenses with known structures, which served as corneal models, under different chamber pressures using ultra-high-speed (UHS) Scheimpflug imaging. METHODS: Three hydrophilic contact lenses were mounted on a sealed water chamber with precisely adjustable pressure: TAN-G5X (41% hydroxyethylmethacrylate/glycolmethacrylate, 550 µm thick), TAN-40 (62% hydroxyethylmethacrylate, 525 µm thick) and TAN-58 (42% methylmethacrylate, 258 µm thick). Each model was tested five times under different pressures (5, 15, 25, 35 and 45 mmHg), using ultra-high-speed Scheimpflug imaging during non-contact tonometry. 140 Scheimpflug images were taken with the UHS camera in each measurement. The deformation amplitude during non-contact tonometry was determined as the highest displacement of the apex at the highest concavity (HC) moment. RESULTS: At each pressure level, the deformation amplitude was statistically different for each lens tested (p<0.001, ANOVA). Each lens had different deformation amplitudes under different pressure levels (p<0.001; Bonferroni post-hoc test). The thicker lens with less polymer (TAN-G5X) had a higher deformation (less stiff behavior) than the one that was thinner but with more polymer (TAN-40), when measured at the same internal pressure. The thinnest lens with less polymers (TAN-58) had a lower deformation amplitude (stiffer behavior) at higher pressures than the thicker ones with more polymer (TAN-40 and TAN-G5X) at lower pressures. CONCLUSIONS: UHS Scheimpflug imaging allowed for biomechanical assessment through deformation characterization of corneal models. Biomechanical behavior was more influenced by material composition than by thickness. Chamber pressure had a significant impact on deformation response of each lens.